Invasive procedures in fetal therapy - Muñoz S., Hernán (2015)
Intrauterine therapy or fetal therapy has developed only in the last 30 years. In 1963 Dr. A.W. Liley performed the first intrauterine transfusion in a case of hemolytic disease constituting the first fetal therapy done in history. Afterwards in the 80s new possibilities of percutaneous fetal therapy and open fetal surgery appeared and in the 90s endoscopic fetal surgery. In this chapter we will revise the different types of invasive procedures that include percutaneous therapy and fetal surgery.